Prerequisites for the transformation of the element of national consciousness in the Kazakh worldview at the beginning of the XXI century - Dzhukeeva, B.A.; Imanzhusip, R.N.; Kashaganova, T.U. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the article the prerequisites for the transformation of national consciousness in the Kazakh worldview at the beginning of the 21st century were deeply analyzed, including the main external and internal influencing factors in the stages of the formation of the national consciousness own development path. We hope that the historical foundations of the formation of a new national consciousness of the citizens of Kazakhstan, the modernization of the national consciousness in the context of the globalization process, and the establishment of new principles of national identity will not be ignored and will arouse the interest of scientists dealing with these issues. In the conditions of Kazakhstan independence, social and humanitarian sciences underwent a certain transformation, their role in the modernization of public consciousness is undoubtedly important. Among the relevant historical topics, the performance should highlight innovative issues that were unthinkable recently. In this regard, the relevance of the conceptual direction associated with field civilization is undeniable. The scientific article defines the problem of national cognition, as well as the increasing complexity and dynamics of the social process, which creates the need for their scientific and philosophical reflection.
ХХІ ғасырдың басындағы қазақ дүниетанымындағы ұлттық сана элементін трансформациялаудың алғышарттары
Предпосылки трансформации элемента национального сознания в казахском мировоззрении начала XXI века
Keywords: nation; national consciousness; transformation; Kazakhstan; XXI century; Kazakh; globalization; national identity